Perancangan Aplikasi QR Code Pendaftaran Perizinan Berbasis Android Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bandar Lampung - Ferry Susanto; Khozainuz Zuhri; Fatimah Fahurian; Romi Hendri (Jurnal Teknologi dan Informatika (JEDA), 2022)
Based on the research, it is necessary to have an information media that is quite effective of the public registering permits in Bandar Lampung City. The purpose of the research is to make it easier for applicants who register their licenses of permits at Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bandar Lampung. So the author makes a solution by making a mobile application with a report entitled "Designing an Android-Based Licensing Registration Application at Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kota Bandar Lampung. This application utilizes the QR-Code System which is used for print media applications. The main feature used in this application is the QR-Code feature so that applicants can easily register each application when registering their permits. The system development method uses the waterfall method and the system design uses UML (Unified Modeling Language). In this research, the author makes an android application using react-native.